PENERAPAN PSAK 70 ASET DAN LIABILITAS PENGAMPUNAN PAJAK PADA LAPORAN KEUANGAN: PENERAPAN PSAK 70 ASET DAN LIABILITAS PENGAMPUNAN PAJAK PADA LAPORAN KEUANGAN - Bayu Sarjono (Jurnal Bisnis Terapan, 2020)
ABSTRACT The objective of the research to analyze taxpayers who have received tax amnesty and accounting treatment of the tax amnesty assets and liabilities in the financial statements. Tax amnesty assets and liabilities are presented separately from the other assets and liabilities in the financial statements. The PSAK 70 is also applicable by non-publicily accountable entities that choose to adopt the SAK ETAP (Standar entity without accountability public). The implementation of PSAK 70 by PT. Z related to the recognition, measurement, presentation, and disclosures in accordance with SAK (financial accounting standar). The difference of tax amnesty assets and liabilities is PT. Z recognizes in addition to the retained earnings in the balance sheet. As we know PSAK 70 paragraph 12 which reads concerning net assets that should have from tax amnesty must be recognized in equity as additional paid in capital. That is what makes the difference between accounting and tax presentation Keywords : tax amnesty, tax amnesty assets and liabilities, retained earning, additional paid in capital